Keanekaragaman dan Kelimpahan Jenis Burung di Pusat Restorasi Mangrove Mojo Kabupaten Pemalang - Tamar, Irsyad Muhammad; Baskoro, Karyadi; Hadi, Mochamad; Rahadian, Rully (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2020)
Mojo Mangrove is a forest area located in the tidal area and becomes a habitat for various organisms in it. Mojo mangrove forest is an ecosystem that is a place to live and breed various species of birds, because of the existence of habitat and food that supports. The location of the Mojo mangrove forest which is far from the settlement is a supporting factor which is the reason birds love the habitat. Species diversity and abundance of bird species can reflect the high biodiversity of other wildlife, meaning birds can be used as indicators of forest quality. The purpose of this study was to determine the diversity and abundance of bird species, and determine the status of bird conservation in the Mojo Pemalang Mangrove Restoration Center. The study was conducted from February to April 2019 at the Mojo Mangrove Restoration Center in Pemalang District, using the point count method. The analysis carried out was a species abundance index, a species diversity index, a species evenness index, a similarity index, and the Hutchinson T test. There are 53 species of 27 families. The diversity of bird species is included in the medium category with an index of 1.97 - 2.85. Based on IUCN, there are 49 species of birds included in the Least concern category, 2 species included in the vulnurable that is Javan coucal (Centropus nigrorufus) and Javan myna (Acridotheres javanicus), 2 species included in the Near threatned category that is Oriental darter (Anhinga melanogaster) dan Javan plover (Charadrius javanicus). Based on Law No. 5 In 1990 there were 10 protected bird species.